6m-2=m+3

Simple and best practice solution for 6m-2=m+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6m-2=m+3 equation:


Simplifying
6m + -2 = m + 3

Reorder the terms:
-2 + 6m = m + 3

Reorder the terms:
-2 + 6m = 3 + m

Solving
-2 + 6m = 3 + m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-1m' to each side of the equation.
-2 + 6m + -1m = 3 + m + -1m

Combine like terms: 6m + -1m = 5m
-2 + 5m = 3 + m + -1m

Combine like terms: m + -1m = 0
-2 + 5m = 3 + 0
-2 + 5m = 3

Add '2' to each side of the equation.
-2 + 2 + 5m = 3 + 2

Combine like terms: -2 + 2 = 0
0 + 5m = 3 + 2
5m = 3 + 2

Combine like terms: 3 + 2 = 5
5m = 5

Divide each side by '5'.
m = 1

Simplifying
m = 1

See similar equations:

| (54b-27ab)= | | 2x^2-20=8 | | 3n+8=92 | | 20y=25y^2 | | 5x-11=8x+12 | | 4x-20.65=6.7 | | 3x+y=7xy | | 0.5x+0.1*5x=62.15 | | X^2=11x-56 | | 0.5x+0.1(5x)=62.15 | | 4x-20.65=20.1 | | -6f-9f=15 | | 15c+1c+21c= | | 61h=9.3-3.2h | | 7y-10y+6=9 | | x^3-4x+x+6=0 | | 7k-5=19 | | cot^2x=-2 | | 2(4x-3)+10=-6(-x+1)-12 | | 1600-320x+12x^2=0 | | 0.7x-0.6x-9=6 | | 32=1.60x | | K-16=2 | | 2(x+3)+7=9 | | R+R^2=24 | | (3m+8)3+m= | | X^2-31x-30=0 | | 2(9x-1)=-3(5-9x)+2 | | 3n-5=7n+12 | | 2x^2*3y= | | e/0.6-9=16 | | (0)=-14x+7 |

Equations solver categories